Periodic Surface-Ring Pattern Formation for Hydroxyapatite Thin Films Formed by Biomineralization-Inspired Processes - Han, Yulai (Langmuir : the ACS journal of surfaces and colloids, 2017)
Surface morphology is a key factor that might significantly influence the properties of biomaterials. In this study, periodic surface-ring structures have been constructed for calcium phosphate thin films via biomineralization-inspired crystallization process. The patterned octacalcium phosphate crystals have been obtained on poly(2-hydroxyethyl methacrylate) (PHEMA) matrix in the presence of poly(acrylic acid) (PAA). The patterned surface morphologies of the crystal thin films could be tuned by the amount of PAA additives. In addition, the rapid and topotactic transformation to hydroxyapatite (HAP) thin films with surface-ring structures has also been achieved. This study may provide new strategy toward the design of functional calcium phosphate-based thin-film hybrids